Innervation zones of fasciculating motor units: observations by a linear electrode array - Jahanmiri-Nezhad, Faezeh; Barkhaus, Paul E.; Rymer, William Z.; Zhou, Ping (Frontiers in Human Neuroscience, 2015)
This study examines the innervation zone (IZ) in the biceps brachii muscle in normal subjects and those with amyotrophic lateral sclerosis (ALS) using a 20-channel linear electromyogram (EMG) electrode array. Raster plots of individual waveform potentials were studied to estimate the motor unit IZ. While this work mainly focused on fasciculation potentials (FPs), a limited number of motor unit potentials (MUPs) from voluntary activity of 12 healthy and 7 ALS subjects were also examined. Abnormal propagation of MUPs and scattered IZs were observed in fasciculating units, compared with voluntarily activated MUPs in healthy and ALS subjects. These findings can be related to muscle fiber reinnervation following motor neuron degeneration in ALS and the different origin sites of FPs compared with voluntary MUPs.